ANALYSIS OF THE INFLUENCE OF SHARIA MICROFINANCE INSTITUTIONS AND SHARIA FINANCING INSTITUTIONS ON INDONESIA'S ECONOMIC GROWTH - Riski, Muhammad Riski Anugerah Pratama; Shauqi, Shauqi Aditya Khalis (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2023)
ANALYSIS OF THE INFLUENCE OF SHARIA MICROFINANCE INSTITUTIONS AND SHARIA FINANCING INSTITUTIONS ON INDONESIA'S ECONOMIC GROWTH Abstract: Purpose: This research aims to analyze the influence of Islamic Microfinance Institutions (LKMS) and Sharia Financing Institutions (LPS) on Indonesia's economic growth from 2015 to 2021. The study explores whether these institutions have a simultaneous and partial impact on economic development during this period. Design/methodology/approach: The research employs a quantitative approach, utilizing multiple linear regression analysis. Data for the study includes the development of assets for LKMS and LPS, as well as Gross Domestic Product (GDP) at constant prices, representing economic growth variables from 2015 to 2021. Findings: The analysis reveals that both LKMS and LPS simultaneously influence economic growth. Specifically, LKMS has a positive and significant impact on economic growth, while LPS shows a positive but insignificant influence on Indonesia's economic growth from 2015 to 2021. The fluctuation in the relationship with LPS is attributed to the possibility of financing being directed towards non-productive, consumptive purposes. Research limitations/implications: The study acknowledges certain limitations, such as the potential non-uniform impact of LPS on economic growth due to a focus on consumptive financing. The findings suggest the need for further exploration into the specific nature of financing activities to enhance productivity in the real sector. Practical implications: The results provide valuable insights for policymakers and stakeholders in the Islamic finance sector. Understanding the differential impact of LKMS and LPS on economic growth allows for targeted strategies to optimize their contributions to Indonesia's economic development. Keywords: Islamic Microfinance Institutions; Sharia Financing Institutions; Economic Growth; Non-Bank Sharia Financial Industry. ANALISIS PENGARUH LEMBAGA KEUANGAN MIKRO SYARIAH DAN LEMBAGA PEMBIAYAAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI INDONESIA Abstrak: Tujuan: Penelitian ini bertujuan untuk menganalisis pengaruh Lembaga Keuangan Mikro Syariah (LKMS) dan Lembaga Pembiayaan Syariah (LPS) terhadap pertumbuhan ekonomi Indonesia dari tahun 2015 hingga 2021. Studi ini mengeksplorasi apakah lembaga-lembaga ini memiliki dampak simultan dan parsial pada pembangunan ekonomi selama periode ini. Desain / metodologi / pendekatan: Penelitian ini menggunakan pendekatan kuantitatif, menggunakan analisis regresi linier ganda. Data untuk penelitian meliputi pengembangan aset untuk LKMS dan LPS, serta Produk Domestik Bruto (PDB) dengan harga konstan, yang mewakili variabel pertumbuhan ekonomi dari 2015 hingga 2021. Temuan: Analisis menunjukkan bahwa LKMS dan LPS secara bersamaan mempengaruhi pertumbuhan ekonomi. Secara khusus, LKMS memiliki dampak positif dan signifikan terhadap pertumbuhan ekonomi, sedangkan LPS menunjukkan pengaruh positif namun tidak signifikan terhadap pertumbuhan ekonomi Indonesia dari tahun 2015 hingga 2021. Fluktuasi hubungan dengan LPS disebabkan oleh kemungkinan pembiayaan diarahkan pada tujuan yang tidak produktif dan konsumtif. Keterbatasan / implikasi penelitian: Studi ini mengakui keterbatasan tertentu, seperti potensi dampak LPS yang tidak seragam terhadap pertumbuhan ekonomi karena fokus pada pembiayaan konsumtif. Temuan ini menunjukkan perlunya eksplorasi lebih lanjut ke dalam sifat spesifik dari kegiatan pembiayaan untuk meningkatkan produktivitas di sektor riil. Implikasi praktis: Hasilnya memberikan wawasan berharga bagi pembuat kebijakan dan pemangku kepentingan di sektor keuangan Islam. Memahami dampak diferensial LKMS dan LPS terhadap pertumbuhan ekonomi memungkinkan strategi yang ditargetkan untuk mengoptimalkan kontribusi mereka terhadap pembangunan ekonomi Indonesia. Kata kunci: Lembaga Keuangan Mikro Syariah; Lembaga Pembiayaan Syariah; Pertumbuhan Ekonomi; Industri Keuangan Syariah Non Bank.